2011
DOI: 10.2337/dc11-0830
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Nocturnal Hypertension in Children and Adolescents With Type 1 Diabetes

Abstract: OBJECTIVEDiabetes is associated with atherogenic risk factors. Hypertension has a major influence on cardiovascular disease in diabetic patients. Ambulatory blood pressure monitoring (ABPM) is useful for identifying nocturnal hypertension. Carotid intima-media thickness (cIMT) is a good measure for identifying subclinical atherosclerosis. This study aimed to evaluate whether nocturnal hypertension affects atherosclerosis in children and adolescents with type 1 diabetes and to investigate the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 25 publications
5
54
1
3
Order By: Relevance
“…Pediatric patients with casual prehypertension may demonstrate abnormalities on ABPM intermediate between normotensive and truly hypertensive people, 78 and some studies have demonstrated subtle signs of target-organ damage in patients with prehypertension, including LVM values similar to youths with sustained hypertension, 34 lower glomerular filtration rate, and increased urine protein excretion, 79 as well as higher cIMT than normotensive patients. 80 Patients with prehypertension may also be at higher risk of progressing to sustained hypertension. 12 Although no longitudinal ABPM studies have been performed to evaluate the risk of progression of prehypertension, such studies could clarify the importance of prehypertension by providing more careful phenotyping of the BP patterns that produce the highest risk of progression to sustained hypertension.…”
Section: Usefulness Of Abpm To Classify Bpmentioning
confidence: 99%
“…Pediatric patients with casual prehypertension may demonstrate abnormalities on ABPM intermediate between normotensive and truly hypertensive people, 78 and some studies have demonstrated subtle signs of target-organ damage in patients with prehypertension, including LVM values similar to youths with sustained hypertension, 34 lower glomerular filtration rate, and increased urine protein excretion, 79 as well as higher cIMT than normotensive patients. 80 Patients with prehypertension may also be at higher risk of progressing to sustained hypertension. 12 Although no longitudinal ABPM studies have been performed to evaluate the risk of progression of prehypertension, such studies could clarify the importance of prehypertension by providing more careful phenotyping of the BP patterns that produce the highest risk of progression to sustained hypertension.…”
Section: Usefulness Of Abpm To Classify Bpmentioning
confidence: 99%
“…Lande et al [20], found that IMT correlated with higher daytime SBP index (measured with ambulatory BP monitoring) which indicates more severe HTN. Other investigators have related 24-hour ambulatory BP monitoring measures to IMT, including a study of youth with type 1 diabetes mellitus where adolescents with reduced nocturnal BP dipping were found to have a thicker IMT [21]. Children with chronic kidney disease (CKD) have also been found to have a thicker cIMT than age-matched controls [22].…”
Section: How Do We Measure Vascular Function In Pediatric Patients Anmentioning
confidence: 99%
“…And cardiovascular disease is based on atherosclerosis (AS), the hallmark of cardiovascular diseases, which is the leading cause of mortality all over the world. Many studies reported that patients with diabetes have 2 to 10 times increased risk of developing atherosclerotic disease (Atabek, Akyürek, Eklioglu, & Alp, 2014;Lee et al, 2011;Pozza, Netz, Schwarz, & Bechtold, 2010;Tantawy, Adly, El Maaty, & Amin, 2009). Carotid intima-media thickness (CIMT) level is the symbol of early atherosclerosis, it has been shown to be the marker of preclinical atherosclerosis (Gimenez et al, 2010), and measurement of the CIMT is independently associated with an increased cardiovascular disease (Atabek, Pirgon, Kurtoglu, & Imamoglu, 2006).…”
Section: Introductionmentioning
confidence: 97%